Detection of Lupeol in Calendula Officinalis Grown in Iraq by GC-MS Analysis - Noor Ali Kadhim; Widad M K Al-Ani; Ibrahem S. Al-Joboury (College of Pharmacy / Mustansiriyah University, 2019)
Triterpenes are abundant group of natural compounds with important structural components of plant's cell membranes. Free triterpenes stabilize phospholipid bilayers in plant cell membranes just as cholesterol does in animal cell membranes. Lupeol is a pentacyclic trite- rpene reported to have important physiological and therapeutic effects in human health issues, therefore its extraction from Calendula officinalis flowers and detection by GC-MS is of significant importance.